Answer:
y = (2x + 3)(2x + 3) = (2x + 3)²
Explanation:
We are given a quadratic function and we have to write it in factored form.
y = 9 + 12x + 4x²
y = 4x² + 12x + 9
We can break the mid-term in such a way that when they are multiplied, the factors give a product of 36x² and when added, they give a result of 12x, as show below:
y = 4x² + 6x + 6x + 9
Taking 2x common from the first two variables and 3 from the second two
y = 2x(2x + 3) + 3(2x + 3)
Taking 2x+3 common
y = (2x + 3)(2x + 3) = (2x + 3)²